2012
DOI: 10.1259/dmfr/21276789
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of foramen magnum in gender determination using helical CT scanning

Abstract: It can be concluded that the reconstructed CT image can provide valuable measurements for the FM and could be used for sexing when other methods are inconclusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
103
15
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(143 citation statements)
references
References 14 publications
19
103
15
6
Order By: Relevance
“…Although some studies suggested these did not have a correlation with the sagittal and the transverse diameter of the FM [43], other studies reported a sexual dimorphism for FM dimensions with all parameters being significantly higher in males [44]. Kamath et al [45] found sex predictability (higher values in males) for FM area (70.3%), followed by sagittal diameter (69.6%), and least for transverse diameter (66.4%), similar to the study of Uthman et al [46] for FM area and Raghavendra Babu et al [47] with higher predictability for FM area and sagittal diameter compared to transverse diameter [9]. Rai et al [48] found OC and FM dimensions higher in males compared to females No stastistically significant difference was found in adults for different age groups for the OC [49] and FM [50].…”
Section: Far Lateral Approachsupporting
confidence: 64%
“…Although some studies suggested these did not have a correlation with the sagittal and the transverse diameter of the FM [43], other studies reported a sexual dimorphism for FM dimensions with all parameters being significantly higher in males [44]. Kamath et al [45] found sex predictability (higher values in males) for FM area (70.3%), followed by sagittal diameter (69.6%), and least for transverse diameter (66.4%), similar to the study of Uthman et al [46] for FM area and Raghavendra Babu et al [47] with higher predictability for FM area and sagittal diameter compared to transverse diameter [9]. Rai et al [48] found OC and FM dimensions higher in males compared to females No stastistically significant difference was found in adults for different age groups for the OC [49] and FM [50].…”
Section: Far Lateral Approachsupporting
confidence: 64%
“…In the Spanish population, the surface area of the males and females were 888.4mm 2 and 801.0mm 2 respectively whereas in Turkish population the males and females were 909.91mm 2 and 819.01mm 2 respectively. 2,20 The surface area of the foramen magnum in the Iraq population it was much lower than the present study where it was 765.2mm 2 in males and 670.2mm 2 in females [21]. Thus, the morphometry of the foramen magnum shows sexual dimorphism and the ethnic variance.…”
Section: 13contrasting
confidence: 50%
“…2 [21].The studies done on the circumference of foramen magnum was very limited. So could not compare with other ethnic populations.…”
Section: 13mentioning
confidence: 99%
“…Several measurements of the skull such as the length, height, and circumference of the head, mastoid process, occipital condyle, and foramen magnum (FM) have been used for this analysis in previous studies (4)(5)(6)(7)(8)(9)(10). The FM is a three-dimensional aperture within the basal central region of the occipital bone (11) and also is a transition zone between the spine and skull.…”
Section: Introductionmentioning
confidence: 99%
“…Two-dimensional imaging methods including antero-posterior and lateral cephalometric radiographs have been generally used in previous studies for skull measurements (18). The use of three-dimensional radiographic images like medical computed tomography (CT) has become more common in recent years (6,(20)(21)(22)(23). To the best of our knowledge, there is only one study regarding the evaluation of FM with cone-beam computed tomography (CBCT) (24).…”
Section: Introductionmentioning
confidence: 99%